A case report about gangrenous sigmoid volvulus in 11-year-old girl - Abdelazeem Hamed Hassan (Elsevier, 2018)
Sigmoid volvulus is a life-threatening condition which requires early diagnosis and immediate surgical intervention. It should be one of the differentials considered in patients presenting with chronic constipation, abdominal distension, and signs of intestinal obstruction. This condition is prevalent all over the world with a greater probability of affecting the elderly with co-morbidities; it is rare in children and adolescents. Sigmoid volvulus is a leading cause of acute colonic obstruction in South America, Africa, Eastern Europe, and Asia. It is rare in developed countries such as USA, UK, Japan, and Australia [1]. We had a case of gangrenous sigmoid volvulus in an 11-year-old girl who presented with abdominal pain, vomiting, abdominal distention, and constipation with symptoms of toxicity. After performing a chest and abdominal X-ray, the case was diagnosed as a sigmoid volvulus. The team performed Hartmann's procedure after the patient resuscitated. The patient developed a surgical site infection during the postoperative period and was discharged with a plan to reverse the colostomy after three months. This case presentation will serve to highlight this example of delayed presentation of sigmoid volvulus. The clinical presentation, radiological and intra-operative findings and management are discussed. Keywords: Sigmoid volvulus, Sigmoidoscopic decompression, Hartmann's procedure